The simulation of bridge pier planning using Revit: A building information modelling approach - Ricardo, Vincent Aluna; Rifai, Andri Irfan; Ginting, Jody Martin; Prasetijo, Joewono (International Journal Labs, 2024)
Building Information Modeling (BIM) represents a transformative approach to architectural design and construction management globally (Babalola, 2023). The construction industry is increasingly recognizing BIM's potential to mitigate project risks, improve cost estimation accuracy, and enhance regulatory compliance. This study highlights how BIM can enhance predictive maintenance, lifecycle cost analysis, and sustainability metrics in bridge infrastructure. Revit's BIM framework empowers engineers to innovate, streamline workflows, and deliver sustainable infrastructure solutions that meet evolving societal needs. The research methodology employed in this study involves systematically collecting data from online sources and using Revit for practical application. The combination of data from Google Scholar and practical application through Revit enhances the robustness and applicability of the research findings. Embracing BIM in bridge pier planning not only enhances project efficiency but also sets a benchmark for future advancements in civil engineering practices.